Opposition to abortion related to inaccurate beliefs about fetal pain perception in utero. (24th April 2021) - Harcourt, Emma; Bering, Jesse; Gullam, Joanna
Abstract : Background: Misinformation about abortion and pregnancy is common. Restrictions on abortion access at and beyond 20 weeks are frequently justified using the claim that a fetus can experience pain before the third trimester. The current medical consensus is that it is unlikely that fetal pain perception is possible before the 29th or 30th weeks of pregnancy. Aims: To examine the relationship between abortion attitudes and beliefs about when a fetus develops the capacity to perceive pain in utero. Methods and Materials: We used Amazon's Mechanical Turk to recruit participants residing in the United States ( N  = 374) and used an online questionnaire to assess their beliefs about abortion and the ability of a fetus to perceive pain. Results: Anti‐choice participants were more likely than pro‐choice participants to believe that a fetus in utero can perceive pain before the 23rd week of pregnancy (63.4 vs. 48.5%, P  = 0.010) and in the first trimester (40.1 vs. 15.8%, P  < 0.000). Most Black and Catholic participants, along with those with advanced degrees, believed that fetal pain is not possible before the third trimester. Conclusions: Most participants believed that a fetus develops the capacity to perceive pain earlier than developmental reality, and this belief correlates with anti‐choice views.